The Italian Renaissance in its historical background - Hay, Denys (Cambridge University Press, 1977)
Professor Hay provides a clear picture of what the Renaissance was, what it meant and how it spread. He shows the Renaissance as a growing and changing series of attitudes and ideas, rooted firmly in the general history of the period, and not as a static and isolated phenomenon. Most current ideas of the Italian Renaissance are derived from Burckhardt's Civilization of the Renaissance in Italy, published in 1860. Professor Hay provides a completely fresh appraisal which goes back to the basic texts, to the great monuments of art and architecture, to the men - Boccaccio, Petrarch and the others - and their achievements: the essence of which historical movements are made. He has taken note of recent Italian scholarship and provides a fresh and readable account of one of the great epochs in European history. There is no other book in English, except the translation of Burckhardt, which embraces the political history of the Renaissance period as well as the history of art and ideas. The book will appeal to the general reader as well as to students of history and art. In this second edition, which has been revised and brought up to date by the author, a more ample treatment of the 'reception' of the Renaissance in England is given in the concluding chapter.